Idiopathic Multicentric Castleman Disease following SARS-CoV-2 Vaccination - Chien-Yu Ker; Hung-Wei Liu; Yu-Chieh Su; Pang-Yu Lai* (Journal of Cancer Research and Practice)
Idiopathic multicentric Castleman disease (iMCD) is a rare lymphoproliferative disorder. The preferred primary treatment for iMCD is siltuximab, an anti-interleukin-6 antibody (anti–IL-6). Chemotherapy is reserved for severe cases or when anti-IL-6 is unavailable. The increased IL-6 signaling in iMCD, increase in IL-6 after mRNA vaccines, and hyperactivation of IL-6 as a critical mediator in COVID-19 infection demonstrate a shared mechanism underlying inflammatory cytokine dysregulation. Herein, we present a case of iMCD after receiving a SARS-CoV-2 vaccination who was treated with traditional chemotherapy over the preferred siltuximab.